Creation and tidal advection of a cold salinity front in Storfjorden: 1. Polynya dynamics. Issue 7 (11th July 2013) - Skogseth, Ragnheid; McPhee, Miles G.; Nilsen, Frank; Smedsrud, Lars H.
Abstract : [1] Hydrographical measurements from the Storfjorden polynya document the presence of an abrupt front in near‐freezing water dividing saline water recently created by a polynya event, from less saline water originating further south. This event occurred days before the survey with estimated heat flux ∼400 W m −2 over the polynya. Brine‐enriched shelf water (BSW) is observed downslope toward deeper parts of Storfjorden, and BSW from earlier polynya events overflows the sill. Current measurements from a nearby sound, Freemansundet, document tidal currents exceeding 80 cm s −1 that displaced the front back and forth beneath the measurement site on fast ice ∼400 m from the polynya edge. Front displacement of ∼12 km is documented and mainly due to the M2 component superimposed on a mean residual current of 0.28 m s −1 into the sound induced by southerly wind during the survey. Complex topography imposes baroclinic tidal currents with strong vertical shear in the fast ice‐covered sound, and with significant cross‐channel flow. Supercooling events indicated in the hydrographical time series, and likely enhanced frazil ice production, are associated with double‐diffusive turbulent mixing when the salinity front passes. In this way, these measurements indicate a novel ice production process along the edge of tidally induced latent heat polynyas where salinity fronts are generated. Turbulence increases (decreases) during flood (ebb) due to the destabilization (stabilization) of the water column when the salinity front passes the measurement site. Double‐diffusive turbulent mixing related to tidal advection of salinity front below fast ice is pursued in a companion paper. Key Points: Polynya response in a tidal regime with shear asymmetry during flood and ebb Salinity front and down‐flow of saline, near‐freezing polynya water Front advection under fast ice leads to supercooling and frazil ice formation